Peningkatan Kecakapan Digital Pada Guru TK dan SD Kanisius Sengkan Yogyakarta - Olivia Lewi Pramesti; Y. Didit Setiawan (Jurnal Atma Inovasia, 2026)
Children of kindergarten and primary school age are often referred to as digital natives are often referred to as ‘digital natives’, as they are well-acquainted with the world of technology. Technological advancements bring both positive and negative impacts. The negative effects on children are a particular concern for teachers as educators in schools. In this digital age, children need guidance to enhance their moral values, character development, ethics, and emotional well-being. Educators are at the forefront of helping children develop good character in this society 5.0 era. This community service initiative aims to enhance the digital literacy of educators, particularly teachers at Kanisius Sengkan Kindergarten and Primary School, regarding children’s digital safety. This initiative is a new and first-of-its-kind activity for educators in that school. The evaluation results indicate that this initiative is highly significant for educators as it broadens their horizons.